2018
DOI: 10.1002/em.22243
|View full text |Cite
|
Sign up to set email alerts
|

Using a gene expression biomarker to identify DNA damage‐inducing agents in microarray profiles

Abstract: High‐throughput transcriptomic technologies are increasingly being used to screen environmental chemicals in vitro to provide mechanistic context for regulatory testing. The TGx‐DDI biomarker is a 64‐gene expression profile generated from testing 28 model chemicals or treatments (13 that cause DNA damage and 15 that do not) in human TK6 cells. While the biomarker is very accurate at predicting DNA damage inducing (DDI) potential using the nearest shrunken centroid method, the broad utility of the biomarker usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
35
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 33 publications
(37 citation statements)
references
References 35 publications
1
35
0
Order By: Relevance
“…Overall, the addition of Running Fisher test improved the sensitivity of TGx-DDI using qPCR. The results indicate that using the TGx-DDI biomarker in the context of the Running Fisher test might be advantageous for high throughput screening to identify DDI agents through assessment of gene expression by qPCR, similar to our previous studies using microarray and nCounter data (Corton et al, 2018).…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Overall, the addition of Running Fisher test improved the sensitivity of TGx-DDI using qPCR. The results indicate that using the TGx-DDI biomarker in the context of the Running Fisher test might be advantageous for high throughput screening to identify DDI agents through assessment of gene expression by qPCR, similar to our previous studies using microarray and nCounter data (Corton et al, 2018).…”
Section: Discussionsupporting
confidence: 83%
“…The use of the Running Fisher test to determine the predictive accuracy of the original TGx-DDI biomarker has been described (Corton et al, 2018). Briefly, the TGx-DDI transcriptomic biomarker was uploaded to the BaseSpace Correlation Engine database (URL: https://www.illumina.com/products/bytype/informatics-products/basespace-correlation-engine.html; formally Next-Bio) (Kupershmidt et al, 2010) and compared to each list of fold changes The 24 chemicals and the concentrations shown above were previously described by Li et al (2017).…”
Section: Chemical Classification By the Running Fisher Testmentioning
confidence: 99%
“…TK6, a lymphoblastoid cell line, is not metabolically competent. Using TK6 in the presence of rat liver S9 microsomal fraction enabled robust DDI classification for those chemicals requiring metabolic activation by TGx-DDI (Buick et al, 2015;Corton et al, 2018). In addition, studies showed that TGx-DDI successfully classified DDI and non-DDI compounds in a gene expression data set from cultured HepaRG cells treated with a variety of compounds (Buick et al, 2015).…”
Section: Technology and Cell System Compatibility Of The Tgx-ddi Biommentioning
confidence: 99%
“…Corton et al demonstrated how the TGx-DDI biomarker could be used to rapidly screen large compendia of transcriptional profiles to identify toxicants that are potentially DDI (Corton et al, 2018). In this example, expression profiles from a commercially available gene expression database called BaseSpace Correlation Engine (BSCE) (https://www.illumina.…”
Section: Case Examplementioning
confidence: 99%
“…Using the search strategy as outlined in the Methods section, 9 different studies published between 2010 and 2018 were identified. Of these, 7 studies provided raw data or DEG lists and thus appeared suited for further analysis (Ates et al, 2018;Corton, Williams, & Yauk, 2018;Doktorova et al, 2013;Doktorova et al, 2014;Dumont et al, 2010;Jennen et al, 2010;Jetten, Kleinjans, Claessen, Chesné, & van Delft, 2013;Josse et al, 2012;Tryndyak et al, 2018). A list of these publications and important basic information about the studies and approaches is presented in Table 1.…”
Section: Literature Search For Heparg Transcriptomics With Genotoximentioning
confidence: 99%